2006
DOI: 10.1111/j.1399-3038.2006.00456.x
|View full text |Cite
|
Sign up to set email alerts
|

The vitamin D slant on allergy

Abstract: Oral vitamin D supplementation has been introduced into modern medicine to prevent rickets without the knowledge that this may have profound immunological consequences. The main vitamin D metabolite calcitriol suppresses dendritic cell maturation and consecutive Th(1) cell development, which has independently described as a key mechanism of allergy development. Animal studies and epidemiological surveys now provide a first link of early vitamin D supplementation and later allergy where several vitamin D regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 107 publications
1
66
0
1
Order By: Relevance
“…Although most reports suggest a role for vitamin D in asthma control, others show that vitamin D may promote, rather than ameliorate, the asthma phenotype. 42,43 These differences have also been reported regarding the effects of vitamin D on Th2 cell responses. One study addressing this issue reported that vitamin D supplementation through the first year of life (2,000 IU/d) elicited an increased rather than decreased risk of developing atopy, allergic rhinitis, and asthma in adulthood.…”
Section: F Enomentioning
confidence: 90%
“…Although most reports suggest a role for vitamin D in asthma control, others show that vitamin D may promote, rather than ameliorate, the asthma phenotype. 42,43 These differences have also been reported regarding the effects of vitamin D on Th2 cell responses. One study addressing this issue reported that vitamin D supplementation through the first year of life (2,000 IU/d) elicited an increased rather than decreased risk of developing atopy, allergic rhinitis, and asthma in adulthood.…”
Section: F Enomentioning
confidence: 90%
“…Vitamin D has been shown to inhibit the maturation of dendritic cells and impede the development of T-helper 1 responses. In theory, vitamin D therefore could increase the risk of allergic disorders in infancy [103]. This is supported by a recent German birth cohort study (LINA study) which found that high vitamin D levels during pregnancy and at birth were associated with an increased risk of food allergy [104].…”
Section: Vitamin D Hypothesismentioning
(Expert classified)
“…Intraperitoneal administration of RvE E1 in mice was observed to decrease airway eosinophil and lymphocyte recruitment, a specific Th2 cytokine, IL-13, ovalbumin-specific IgE, and AHR to inhaled methacholine [45]. RvE1 promoted the resolution of inflammatory airway responses in part by directly suppressing the production of IL-23 and IL-6, which promote the survival and differentiation of IL-17-producing T helper cells in the lung [ [58,59]. 1,25-dihydroxyvitamin D3 (1,25(OH)2 D3) potentiates the efficacy of immunotherapy, and the regulatory cytokines IL-10 and TGF-beta play a crucial role in the effector phase of this mouse model [60].…”
Section: Effects On Inflammatory Cells and Cytokinesmentioning
confidence: 99%